Advanced applications of DNA nanostructures dominated by DNA origami in antitumor drug delivery - Zhang, Yiming; Tian, Xinchen; Wang, Zijian; Wang, Haochen; Liu, Fen; Long, Qipeng; Jiang, Shulong (Frontiers in Molecular Biosciences, 2023)
DNA origami is a cutting-edge DNA self-assembly technique that neatly folds DNA strands and creates specific structures based on the complementary base pairing principle. These innovative DNA origami nanostructures provide numerous benefits, including lower biotoxicity, increased stability, and superior adaptability, making them an excellent choice for transporting anti-tumor agents. Furthermore, they can considerably reduce side effects and improve therapy success by offering precise, targeted, and multifunctional drug delivery system. This comprehensive review looks into the principles and design strategies of DNA origami, providing valuable insights into this technology' s latest research achievements and development trends in the field of anti-tumor drug delivery.Additionally, we review the key function and major benefits of DNA origami in cancer treatment, some of these approaches also involve aspects related to DNA tetrahedra, aiming to provide novel ideas and effective solutions to address drug delivery challenges in cancer therapy.